Penggunaan Media Gambar dalam Pembelajaran Kosakata di MTs Nurul Ulum - Afifah Shofia Faradisa; Laily Fitriani (INAIFAS PRESS, 2023)
The research was conducted at MTs Nurul Ulum with the aim of determining the problems of vocabulary learning and its causal factors and describing the steps of vocabulary learning with image media. The method used by the researcher was a qualitative method with a descriptive approach. The results of the study were: (1) The objectives of vocabulary learning at MTs Nurul Ulum were not achieved properly. This happened because the previous learning carried out online was less specific and there were some students who graduated from elementary school (SD) who had never studied Arabic. In addition, students' interest and motivation in learning were still low and teachers had not used learning media other than teacher books and student books, and (2) vocabulary learning with image media using the stages of exploration, organizing, elaboration, confirmation, and reinforcement of the material. In this way the image media can be an instrument to support students' success in learning Arabic.